Cytotoxicity of eurycoma longifolia root extract on female adenocarcinoma cell lines - Abdullah, 'Afif Raihan; Abdul Rahman, Suzanah; Kaderi, Mohd Arifin; Chan, Kit-Lam; Abdul Samat, Nadia Hanis; Ahmad, Nur Amalina; Zahri, Syazana (2017)
Introduction Cervical and ovarian cancers are lethal gynaecological malignancies among women in Malaysia. Eurycoma longifolia is widely used as herbal remedy and natural health supplement. It would be interesting to examine the effects of extracts from this natural product on significant cancers that affect the local health scene. The current study is designed to investigate the effects of Eurycoma longifolia on cervical (HeLa), ovarian (Caov-3) cancer and normal human ovarian surface epithelial (nHOSE) cell line in comparison with cisplatin.